Measuring real-time violence exposure and its impact on intimate partner violence perpetration among adolescents - Rachel Kidman; Janan Janine Dietrich; Xiaoyue Zhang; Candice W. Ramsammy; Phumla Madi; Stefanie Vermaak; Buisiwe Nkala-Dlamini; Avy Violari (PLoS ONE, 2025)
Background Intimate partner violence (IPV) has dire health consequences. To intervene, it is critical we first understand why young men perpetrate IPV. One theory is that men who experience violence are more likely to perpetrate violence. We used real time data to examine how daily and repeat experiences of violence affect IPV behaviors. Methods We enrolled 498 males aged 15-19 years in Soweto, South Africa during 2020-2022. We collected data through weekly mobile phone surveys (n = 12,603) delivered over a year. Generalized linear mixed effect models were used to fit IPV perpetration as a function of past-24-hour violence victimization; models included indicators for between-person and within-person components of victimization. Findings In at least one survey submitted, 13% of boys reported perpetrating physical IPV and 5% perpetrating sexual IPV. Any victimization in the past 24-hours significantly increased the odds of physical (OR 4.00) and sexual violence perpetration (OR 2.45). When examined individually, sexual violence victimization had the strongest association (OR of 7.96 for physical and 4.88 sexual IPV perpetration). We also examined the between-person influence of victimization. Boys who experienced more violence on average (a higher person-centered mean exposure) were substantially more likely to perpetrate both physical IPV and sexual IPV as compared to boys with overall low levels of victimization. Conclusion Adolescent boys who experience violence are more likely to use violence against their partners that same day. To break this cycle, it will be critical to understand the mechanisms by which proximal victimization triggers onward violence perpetration. Both the current findings and the next steps highlight the importance of real-time, repeated data collection.